Nurse-patient dyads linking nurse & patient characteristics to patient satisfaction - Tejero, Lourdes Marie S. (College of Nursing UP Manila, 2009)
Nursing is actualized in an encounter. The nurse's goal of patient's well-being is realized mainly through the interaction between nurse and patient. Such an interaction is not just then an irrelevant occurrence, but a human experience, creating relational links between the nurse and patient. As such, the nurse and patient are no longer separate entities during the interaction, but a dyad. The nurse-patient dyad becomes not just the sum total of the characteristics of the two persons, but an integration of their characteristics working synergistically, thereby bringing about optimum outcomes of care.